Odontogenic sinusitis – case series and review of literature. Issue 1 (26th January 2022) - Garry, S; O'Riordan, I; James, D; Corbett, M; Barry, T; Thornton, M
Abstract: Background: Odontogenic sinusitis is a common cause of rhinosinusitis that is often undiagnosed and overlooked. No single sign or symptom is specific for odontogenic sinusitis, and failure to focus on the specific radiological features can delay diagnosis. Objective: This paper presents four cases of chronic sinusitis that had an odontogenic origin. Each case was referred for a second opinion. Three patients had previously undergone unsuccessful surgical management. Methods: The literature, and the associated contributory clinical, radiological and microbiological features required for correct diagnosis and management, are reviewed. Results: Each case resulted in a positive patient outcome following the involvement of both otolaryngology and maxillofacial surgery departments. Conclusion: A high index of suspicion is advocated for odontogenic sinusitis in cases not responding to standard management plans. Collaboration with a maxillofacial specialist is important for diagnosis and management. This should be considered where standard management fails, or clinical features and radiological signs of odontogenic sinusitis are present. This paper also highlights the need for otolaryngologists to incorporate, at the very least, a basic dental history and examination as part of their assessment in recalcitrant cases.